Report concerning the colaborative study for establish of reference standard eficacity of colistimethat sodium - Simona Sturzu,; Daniela Tirinoaga,; Rodica Stancu,; Georgeta Dan (Medicamentul Veterinar)
Institute for the Control of Veterinary Biological Products and Medicines participated at the collaborativestudy for determine the potency of colistimethate sodium CRS, Lot 2, according to the protocol sent by theEDQM (European Directorate for the Quality of Medicines) - coordinator of the study.The purpose of the study was to determine the potency of the batch 2 colistimethate sodium in thecharacterization of the substance as reference standard.Potency was determined by microbiological method, based on comparing the inhibition zones of growthof micro-organisms sensitive to those of a reference standard, as specified in European Pharmacopoeia"Colistimethate sodium", Chapter 2.7.2. - Microbiological testing of antibiotics.After analysis of received data from participants and their statistical processing by the EDQM, thepotency of the batch 2, colistimethate sodium - reference materials, was established in 285000UI/fiola.